Does the transfer of agricultural labor reduce China’s grain output? A substitution perspective of chemical fertilizer and agricultural machinery - Lu, Hua; Huan, Haoting (Frontiers in Environmental Science, 2022)
The continuous increase in China’s grain output has significantly contributed to food security and poverty alleviation worldwide. Whether the massive nonagricultural transfer of the agricultural labor force in China could affect grain production and the extent of the effects of such changes have become important practical issues. By using panel data from major grain-producing provinces in China from 1995 to 2017 and based on farmer behavior theory, this paper constructs an econometric model and a mediation effect model to empirically test the influencing mechanism and causal relationship between agricultural labor force transfer (ALT) and grain output from the substitution perspective of chemical fertilizer and agricultural machinery application. The findings reveal that ALT has no substantial negative impact on China’s grain output but is conducive to promoting grain production. ALT can directly promote grain production and partially promote it through the use of agricultural machinery and the application of chemical fertilizers as mediation variables. These findings have important policy implications for promoting grain production and the nonagricultural transfer of the agricultural labor force in China. Moreover, this work can improve the international community’s understanding of the seventeen consecutive increases in China’s grain output and provide a reference for grain production worldwide. In the future, a heterogeneity analysis can be carried out in grain main-marketing areas and producing and marketing balance areas in China, and the relationship between agricultural machinery and the environment is worthy of further studies.